How do organizations implement an effective LSS initiative? A qualitative study. Issue 5 (2nd May 2020) - Sony, Michael; Antony, Jiju; Naik, Subhash
Abstract : Purpose: Lean Six Sigma (LSS) is one of the most popular and widely used business improvement methodologies. However, many organizations discontinue LSS despite a plethora of studies on the critical success factors. The purpose of this study is to answer the research question how do organizations implement an effective LSS initiative? Design/methodology/approach: Qualitative study is conducted on managers working in companies using LSS for a long time. The data were analysed using Colaizzi method. Findings: Twelve factors were identified which were responsible for the effective implementation of LSS. They are financial performance, organization-wide LSS culture, organization-wide innovation culture, continuous training and retraining of employees on LSS, continuous top management support, linking LSS to business strategy, linking LSS to the customer, project selection strategy, communication, recognition and compensation systems, social benefits and green benefits. Originality/value: This is the first study to investigate the effective implementation of LSS initiative in the organization.